Ergodic theorems for homogeneous generalized stochastic fields and homogeneous stochastic fields on groups - Tempelman, A. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. А. Темпельман, Эргодические теоремы для однородных обобщенных случайных полей и однородных случайных полей на группах A. Tempelmanas, Ergodinės teoremos homogeniniams apibendrintiems atsitiktiniams laukams ir homogeniniams atsitiktiniams laukams grupėse